Critical Analysis of the Supreme Court Decision Number 63/PUU-XIX/2021 Regarding Sold Flat of Copyrights - Ester Renata Patricia; Gratianus Prikasetya Putra (Dinasti Research, 2025)
This article is titled Critical Analysis of The Supreme Court Decision Number 63/PUU-XIX/2021 regarding Sold Flat of Copyright which criticizes about The Law of The Republic of Indonesia Number 28 of 2014, hereinafter referred as UUHC, especially in Article 18 and 122. The aim of this research is to analyze the concept of sold flat in UUHC which is contradictory compared to common knowledge and its relevance to the law system in Indonesia. The research method used in this writing is a normative juridical research, namely by conducting a literature study. The study shows that the term to return the economic right to the creator after the sold flat contract reaches twenty-five years, is required because the theory which fundamentally underlies the drafting of UUHC was structured to prioritize protecting the creator (subject), not the creation (object). Therefore, instead of forcing that term in UUHC which causes contracditio in terminis, this study provides suggestion to remove the concept of sold flat in UUHC and use the concept of license as the only way for creator to transfer the economic right to be exercised by other parties as Licensee